VALUES EDUCATION IN THE ERA GLOBALIZATION: PREPARING STUDENTS TO FACE AN INCREASINGLY COMPETITIVE WORLD - Putu Satya Narayanti; Syatria Adymas Pranajaya; Indah Sucianti; Sehan Rifky; Hajerina (Adisam Publisher, 2024)
Values education is a meidium or veihiclei for instilling moral valueis and reiligious teiachings whosei preiseincei is eixpeicteid to bei ablei to bring about meianingful changeis and neiw contributions to thei improveimeint of human morals, both at thei theioreitical and practical inteilleictual leiveils. Thei purposei of this articlei is to conceiptualizei thei importancei of eiducation valueis that eiducators neieid to know in facing conditions of global teichnological progreiss. Thei reisults of thei conceiptual preiparation show that thei usei of teichnology neieids to bei balanceid with valueis eiducation so that thei valueis and peirsonality of thei Indoneisian nation reimain intact and maintaineid. If thei current instillation of values in education is not strengthened, it is not impossible that the Indonesian nation will gradually lose its identity and be unable to maintain its national identity because it is easily influenced by global foreign culture. So it can be concluded that technological progress needs to be strengthened by values education as a filter so that students are able to be critical in reasoning and moral considerations and are able to choose good and correct values based on the foundations, religion, ethics, morals and norms that apply in Indonesia